Thermal and centrifugal stresses in curved double wall transpiration cooled components with temperature dependent thermoelastic properties. (January 2022) - Skamniotis, Christos; Cocks, Alan C.F.
Abstract: The integration of double wall transpiration cooling (DWTC) into gas turbines and hypersonic vehicles is key for addressing future needs in aerospace and power generation. This paper identifies the roles of geometric curvature and temperature dependence of thermoelastic properties on stresses in DWTC systems under combined thermal and centrifugal loading. An increase of thermal expansion coefficient, α, with temperature as exhibited by Ni alloys is shown to dominate over the decrease of Young's modulus, E, in double walls, such that the thermal stresses are significantly higher than the case of temperature independent E and α . The effect is generally promoted by the thermal mismatch between the walls; in highly curved systems, the difference in wall circumferences also comes into play. The critical stresses at film holes, impingement holes and pedestals are affected differently for systems with convex and concave hot outer surfaces while the optimal wall thickness ratio is suggested to depend on the severity of thermal loading with respect to centrifugal loading. Our elastic solutions provide the essential information for evaluating the structural integrity of DWTC systems and can be generalised to multiwall systems.